Perspektif Guru Pendidikan Anak Usia Dini Terhadap Pembelajaran Digital di Masa Covid 19 - Sutrisno Sutrisno; Firrdaus Zar’in; Siti Salachah (Jurnal Ilmiah Wahana Pendidikan, 2021)
This article aims to help early childhood education teachers improve their professional competence in responding to ICT developments so that they can utilize digital media for learning activities. The method used is descriptive qualitative, the method used to see and describe the views of early childhood teachers on digital media that can be used in learning activities. The results obtained in this activity were that early childhood education teachers did not understand and did not apply the use of digital media, after being given training on teacher understanding and there was an increase in the use of digital media for the learning process in early childhood education. The conclusion is to make changes in learning during the Covid 19 period, teachers need to obtain knowledge about learning during the Covid 19 period, in which conditions students, teachers, parents and the community must limit social relationships, in order to prevent the spread of the Vovid 19 virus, children Early childhood must continue to learn, so the right and effective learning model is an online learning model using digital media